KAJIAN KONSEPTUAL TENTANG SOCIAL-EMOTIONAL LEARNING (SEL) DALAM PEMBELAJARAN BAHASA - Helaluddin Helaluddin; Alamsyah Alamsyah (AL-ISHLAH: Jurnal Pendidikan, 2019)
In the industrial era 4.0, the students, as one of the main components of education, have many conflicts and problems that brought to the school. That is, student is not only facing problem in academic aspect but also psychology aspect. For this reason, it is necessary to have the right strategy in social emotional learning (SEL) to equip students with the various skills they need in era industrial 4.0. this study was conduct using the Systematic Literature Review (SLR) method for various research results and other sources related to SEL activities. Through language learning, expected pupils to develop a variety of SEL skills, such as: (1) self-awareness, (2) self-management, (3) social awareness, (4) relationship skills, and (5) responsible decision-making. Furthermore, this article also discusses various strategies and language learning program that can be used by teachers in instilling the SEL in the classroom.